Avaliação do reparo periapical após cirurgia parendodôntica por meio de radiografia periapical convencional, digital e tomografia computadorizada em feixe - Jorge, Érica Gouveia [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
This study was divided into two sections, having as individual objectives: (1) - to evaluate the healing of periapical lesion after endodontic surgery, through the comparison among area values measured in digitized conventional and digital radiographs, and Cone Beam computed tomography (CBCT) and (2) - to evaluate the periapical bone repair over different periods of time after endodontic surgery by volume measured in CBCTs, and by percentage values calculated from the conventional and digital radiographs, and CBCTs. Material and Methods: Eleven maxillary anterior teeth, with the presence of periapical lesion were submitted to root-end filling. Conventional and digital radiographs, and CBCTs were taken prior to the surgeries and after 48 h (baseline), 4 and 8 months. For each period, the area (mm 2 ) of the periapical lesion observed in the radiographs was compared to those of CBCTs. The volume of the lesions, at all stages of evaluation, was calculated using the software ImageJ. The radiographic images were also imported into the ImageJ software, and the area of periapical radiolucency was measured. The area in the CBCTs was obtained based on the slice with the greater mesio-distal diameter of the lesion. To calculate the volume, the area of the periapical lesion of each CBCT slice, in a parallel orientation to the sagittal axis of the entire lesion, was calculated. Then, the volume of each slice was calculated by multiplying the area by the distance between the tomographic slices. The values of area (mm 2 ), measured in the radiographs and CBCTs, and volume (mm 3 ), measured in the CBCTs, were used to calculate the percentage of periapical bone repair. The data were submitted to Analyses of Variance (α=0.05), followed by T-tests. Results: A significant effect was observed among the Periods of Evaluation... (Complete abstract click electronic access below)
Keywords: Radiografia; Tomografia; Diagnostico; Endodontia; Tomography